Type 1 autoimmune pancreatitis - Zen Yoh (Orphanet Journal of Rare Diseases, 2011)
Abstract Before the concept of autoimmune pancreatitis (AIP) was established, this form of pancreatitis had been recognized as lymphoplasmacytic sclerosing pancreatitis or non-alcoholic duct destructive chronic pancreatitis based on unique histological features. With the discovery in 2001 that serum IgG4 concentrations are specifically elevated in AIP patients, this emerging entity has been more widely accepted. Classical cases of AIP are now called type 1 as another distinct subtype (type 2 AIP) has been identified. Type 1 AIP, which accounts for 2% of chronic pancreatitis cases, predominantly affects adult males. Patients usually present with obstructive jaundice due to enlargement of the pancreatic head or thickening of the lower bile duct wall. Pancreatic cancer is the leading differential diagnosis for which serological, imaging, and histological examinations need to be considered. Serologically, an elevated level of IgG4 is the most sensitive and specific finding. Imaging features include irregular narrowing of the pancreatic duct, diffuse or focal enlargement of the pancreas, a peri-pancreatic capsule-like rim, and enhancement at the late phase of contrast-enhanced images. Biopsy or surgical specimens show diffuse lymphoplasmacytic infiltration containing many IgG4+ plasma cells, storiform fibrosis, and obliterative phlebitis. A dramatic response to steroid therapy is another characteristic, and serological or radiological effects are normally identified within the first 2 or 3 weeks. Type 1 AIP is estimated as a pancreatic manifestation of systemic IgG4-related disease based on the fact that synchronous or metachronous lesions can develop in multiple organs (e.g. bile duct, salivary/lacrimal glands, retroperitoneum, artery, lung, and kidney) and those lesions are histologically identical irrespective of the organ of origin. Several potential autoantigens have been identified so far. A Th2-dominant immune reaction and the activation of regulatory T-cells are assumed to be involved in the underlying immune reaction. IgG4 antibodies have two unique biological functions, Fab-arm exchange and a rheumatoid factor-like activity, both of which may play immune-defensive roles. However, the exact role of IgG4 in this disease still remains to be clarified. It seems important to recognize this unique entity given that the disease is treatable with steroids.